Rural Students in a Chinese Top-Tier University: Family Background, School Effects, and Academic Performance. Issue 2 (4th March 2017) - Postiglione, Gerard A.; Ailei, Xie; Jung, Jisun; Yanbi, Hong
Abstract: New preferential policies in China promise to increase the number of rural students entering top-tier universities, where there is a wider path to a higher social status. While a substantial body of literature has investigated rural students' trajectories to university, there is a dearth of systematic empirical studies on the academic success of rural students in colleges and universities. This study seek to address this gap by examining the academic achievement of representative samples of students entering an elite university in China, including their place of origin, family background, school experience, and the characteristics that align with their academic performance. The data suggest no significant difference in academic performance obtained by urban and rural students with respect to average grade point average (over four years). It also suggests that fathers' occupations may not be associated with the academic achievements of students from different families. However, the data suggest a relatively clear school effect on the academic performance of students at University S. 1 The study enriches the discussions of the inequality issue in China's higher education sector. It also enriches the literature in sociology of education by looking at the relative strength of the relationship between the possible causes and outcomes of schooling.